Simulation of near field dilution of the submarine outfall of santa marta (colombia) (2013)
The dilution, trajectory and thickness of the buoyant plume formed by wastewater discharge from the submarine outfall of Santa Marta were determined using a near field dilution model and hydrographic data from salinity, temperature and density profiles, as well as from the velocity data at different levels of the water column. The magnitude of the velocity was provided by previous runs of a three-dimensional hydrodynamic model. The results showed that the plume goes through alternating periods of entrapment in the water column or reaching the water surface, according to conditions of upwelling and stratification of the receiving body of water. When the plume comes to the surface, dilution levels greater than 100 are achieved.